Catalytic Ozonation with ZnO Nanoparticles: A Novel Approach to Lignin Degradation in Synthetic Wastewater: 10.32526/ennrj/24/20250017 - Amnath, Yupaporn; Aiyathiti, Chatchaval (Environment and Natural Resources Journal, 2025)
The purpose of this study is to evaluate ZnO nanoparticle-catalyzed ozonation degradation lignin in synthetic wastewater. By applying response surface methodology (RSM) and central composite design (CCD), we analyzed the interaction between key factors and optimized their conditions. pH, ZnO dose, time, and lignin concentration were varied and encoded into a second-order model, with ANOVA confirming its significance (F-value=19.53). The model predicted a 99.99% lignin degradation efficiency under optimal conditions: pH 11, 1.0 g ZnO, 50 minutes, and 50 mg/L lignin. The high correlation (R2=0.9480) validated the model, highlighting the effectiveness of ZnO nanoparticle-catalyzed ozonation for lignin removal.